Observation of the Same New Sheet Topology in Both the Layered Uranyl Oxide-Phosphate Cs11[(UO2)12(PO4)3O13] and the Layered Uranyl Oxyfluoride-Phosphate Rb11[(UO2)12(PO4)3O12F2] Prepared by Flux Crystal Growth - Juillerat, Christian A.; Kocevski, Vancho; Besmann, Theodore M.; zur Loye, Hans-Conrad (Frontiers in Chemistry, 2019)
Single crystals of four new layered uranyl phosphates, including three oxyfluoride-phosphates, were synthesized by molten flux methods using alkali chloride melts, and their structures were determined by single-crystal X-ray diffraction. Cs11[(UO2)12(PO4)3O13] (1) and Rb11[UO2)12(PO4)3O12F2] (2) contain uranyl phosphate layers exhibiting a new sheet topology that can be related to that of β-U3O8, while Cs4.4K0.6[(UO2)6O4F(PO4)4(UO2)] (3) and Rb4.4K0.6[(UO2)6O4F(PO4)4(UO2)] (4) contain layers of a known isomer of the prominent phosphuranylite topology. The location of the fluorine in structures 2-4 is discussed using bond valence sums. First principles calculations were used to explore why a pure oxide structure is obtained for the Cs containing phase (1) and in contrast an oxyfluoride phase for the Rb containing phase (2). Ion exchange experiments were performed on 1 and 2 and demonstrate the ability of these structures to exchange approximately half of the parent alkali cation with a target alkali cation in an aqueous concentrated salt solution. Optical measurements were performed on 1 and 2 and the UV-vis and fluorescence spectra show features characteristic of the UO22+ uranyl group.